The Damaging Growth: An Empiric Evidence of Environmental Kuznets Curve in Indonesia - Darwanto, Darwanto; Woyanti, Nenik; Santosa, Purbayu Budi; Sasana, Hadi; Ghozali, Imam (International Journal of Energy Economics and Policy, 2019)
This study examines the short-run and long-run relationships between economic growth, carbon dioxide (CO2) emissions and energy consumption within a sample period of 1990-2016. The study used Autoregressive Distributed Lag (ARDL) approach to test the cointegration relationship and Granger Vector Error Correction Model (VECM) causality test to investigate the direction of causality. This study does not support the hypothetical relationship (EKC) for a significance level of 5%. The long-run test of Granger causality shows that there is a two-way causal relationship of economic growth, CO2 emissions, and energy consumption. This result indicates that a reduction in energy consumption is an effective way to control CO2 emissions but will simultaneously impede economic growth. Therefore, setting suitable policy related to efficient consumptions of energy resources and renewable energy resources is necessary. Keywords: Environmental Kuznets Curve, CO2 Emissions, Energy Consumption. JEL Classifications : Q42, Q43, C10 DOI: https://doi.org/10.32479/ijeep.7816